Maternal Outcome in Pregnancy with Heart Disease –A Case Control Study - Lamsal, Sunita; Mandal, Praveen; Paudyal, Pooja; Pant, Padam Raj (Journal of National Heart and Lung Society Nepal, 2024)
Background: Cardiac diseases in pregnant women are one of the leading cause of maternal morbidity and mortality. The objective of this study was to find out the maternal outcome in pregnant women with cardiac diseases attending department of Obstetrics & Gynecology, TUTH and Manmohan Cardiothoracic Vascular and Transplant Center (MCTVTC). Methods: This was a hospital based, case control study conducted in Department of Obstetrics & Gynecology, TUTH and Manmohan CTVTC, Maharajgunj, Kathmandu. Pregnant women with preexisting and recently diagnosed heart disease coming to Department of Obstetrics & Gynecology, TUTH and Manmohan CTVTC after fulfilling inclusion and exclusion criteria.Their course in hospital was documented and any complications during the course of pregnancy were noted. Results: There were total of 113 patients of heart disease with pregnancy heart disease so we excluded them and 98 cases were analyzed in one year period with 98 controls. The mean age was similar in both cases and controls group 27.1 and 27.2 years respectively. Comparing the outcome, admission to ICU/CCU was 23 times higher in cases than in control 19:1(OR 23.1(3.5-974.5) with p-value of <0.001), heart failure was 10 times higher in cases 10:1 (OR 10.9 (1.5-482.1) with p value of 0.01) as well as length of hospital stay was higher in cases with mean stay was 6.7:2.5 days with p-value of <0.001. Conclusion: The outcome of pregnant women with heart disease was overall good in our study as there was no mortality. With multidisciplinary efforts all the complications were managed well even though women with heart disease had more adverse events as compared to women without heart disease.